Isolation of fungi from nature in the region of Botucatu, state of São Paulo, Brazil, an endemic area of paracoccidioidomycosis - Montenegro, MR [UNESP]; Miyaji, M; Franco, M [UNESP]; Nishimura, K; Coelho, Kunie Iabuki Rabello [UNESP]; Horie, Y; Mendes, RP [UNESP]; Sano, A; Fukushima, K; Fecchio, Denise [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 1996)
In an attempt to isolate Paracoccidioides brasiliensis from nature 887 samples of soil from Botucatu, SP, Brazil, were collected cultured in brain heart infusion agar supplemented with dextrose, in potato dextrose agar and in yeast extract starch dextrose agar, all with antibiotics, at 25º and 37ºC. Five thermo-dependent dimorphic fungi morphologically resembling P. brasiliensis were isolated; two from armadillo holes; further studies of the biology, antigenicity and genetic features of the five dimorphic fungi are necessary to clarify their taxonomy and their possible relation to P. brasiliensis. In addition, 98 dematiaceous fungi and 581 different species of Aspergillus spp. were also isolated. Our findings emphasize that armadillos and their environment are associated with thermo-dimorphic fungi and confirm the ubiquity of pathogenic dematiaceous fungi and Aspergillus spp.
Keywords: ecology; nature; pathogenic fungi; Paracoccidioides brasiliensis